1991
DOI: 10.1177/070674379103600609
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Pre-Adolescent Suicide in Newfoundland and Labrador

Abstract: This study investigated suicides by people aged ten to 19 in Newfoundland and Labrador from 1977 to 1988. It is the first study of suicide in the province to use the records of death from all eight hospital pathology departments in the province and from the office of the Chief Forensic Pathologist. Cases were selected for the study using standardized criteria, independent of the manner of death recorded on the death certificate. A suicide rate of 4.37 per 100,000 was found. This rate and the age- and sex-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 10 publications
0
9
1
1
Order By: Relevance
“…6 In the Newfoundland and Labrador study, the most common method was firearms (54%), followed by hanging (33%). 4 Statistical analysis failed to demonstrate a significant difference in the use of hanging between the current study and the 4 Canadian studies. However, statistically significant differences were noted regarding the use of firearms between this study and the 3 provincial studies (P Ͻ 0.005) but not the Montreal study.…”
Section: Suicide Methods In Canadacontrasting
confidence: 51%
See 1 more Smart Citation
“…6 In the Newfoundland and Labrador study, the most common method was firearms (54%), followed by hanging (33%). 4 Statistical analysis failed to demonstrate a significant difference in the use of hanging between the current study and the 4 Canadian studies. However, statistically significant differences were noted regarding the use of firearms between this study and the 3 provincial studies (P Ͻ 0.005) but not the Montreal study.…”
Section: Suicide Methods In Canadacontrasting
confidence: 51%
“…5,7 However, there was a trend of decreasing firearm use and increasing numbers of suicides by hanging. In both the Manitoba and Newfoundland and Labrador studies, it was noted that there is a higher incidence of suicides in Native populations 4,5,7 In Ontario, the coroner's reports are not permitted to comment on ethnic origin.…”
Section: Suicide Methods In Canadamentioning
confidence: 96%
“…Ainsi, les incidences de suicide chez les adolescents autochtones de certaines nations nordiques y sont trois fois plus élevées que chez les Eurocanadiens (Aldridge et St-John, 1991 ;Bagley, Wood et Khumar, 1990). Entre autres, la consommation précoce d'alcool et de stupéfiants représente un problème majeur dans les réserves (Adrian, Layne et Williams, 1990 ;Gfellner et Hundleby, 1995 ;Lalinec-Michaud, Subak, Ghadirian et Kovess, 1991).…”
Section: Le Milieu Autochtone Québécois : Réalités Psychosociales Et unclassified
“…It has been suggested that suicide rates are frequently misreported Phillips and Ruth, 1993;Aldridge and St. John, 1991;Cantor and Dunne, 1990;O'Carroll, 1989;Kleck, 1988;Monk, 1987;Pescolido and Mendelsohn, 1986;Malla and Hoenig, 19831. To increase the validity of suicide rates in the present study, deaths in the cohort were isolated into International Classification of Disease (ICD) categories 796 and E800-E989, which included suicides, all types of accidents, poisonings, violence, all external causes, and undetermined causes.…”
Section: Suicide Case Validationmentioning
confidence: 99%